Hands4U: the effects of a multifaceted implementation strategy on hand eczema prevalence in a healthcare setting. Results of a randomized controlled trial. (27th November 2014) - van der Meer, Esther W. C.; Boot, Cécile R. L.; van der Gulden, Joost W. J.; Knol, Dirk L.; Jungbauer, Frank H. W.; Coenraads, Pieter Jan; Anema, Johannes R.
<x xml:space="preserve">Abstract</x> Background Healthcare workers have an increased risk of developing hand eczema. A multifaceted implementation strategy was developed to implement a guideline to prevent hand eczema among healthcare workers. Objectives To investigate the effects of the implementation strategy on self‐reported hand eczema and preventive behaviour. Methods A randomized controlled trial was performed. A total of 48 departments (n = 1649) were randomly allocated to the multifaceted implementation strategy or the control group. The strategy consisted of education, participatory working groups, and role models. Outcome measures were self‐reported hand eczema and preventive behaviour. Data were collected at baseline, and 3, 6, 9 and 12 months of follow‐up. Results Participants in the intervention group were significantly more likely to report hand eczema [odds ratio (OR) 1.45; 95% confidence interval (CI) 1.03–2.04], and they reported significantly less hand washing (B, − 0.38; 95%CI: − 0.48 to − 0.27), reported significantly more frequent use of a moisturizer (B, 0.30; 95%CI: 0.22–0.39) and were more likely to report wearing cotton undergloves (OR 6.33; 95%CI: 3.23–12.41) than participants in the control group 12 months after baseline. Conclusions The strategy implemented can be used in practice, as it showed positive effects on preventive behaviour. More research is needed to investigate the unexpected effects on hand eczema.